2016
DOI: 10.1097/aco.0000000000000303
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based fluid management in the ICU

Abstract: Evidence-based fluid therapy includes a multifaceted diagnostic approach, the primary use of balanced crystalloids and early aggressive (septic) shock resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…It is likely that additional volume fluid loading in our mode, would have been beneficial to hemodynamic recovery. At the bedside, such a clinical pattern should be corrected by individually adapted fluid and vasopressor treatment, even though fluid management remains extremely challenging in patients with septic shock [36]. Consequently, while reduction in heart rate is counterintuitive in instances of hypovolemia, on the contrary, a lower dose of esmolol may appear more appropriate in patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that additional volume fluid loading in our mode, would have been beneficial to hemodynamic recovery. At the bedside, such a clinical pattern should be corrected by individually adapted fluid and vasopressor treatment, even though fluid management remains extremely challenging in patients with septic shock [36]. Consequently, while reduction in heart rate is counterintuitive in instances of hypovolemia, on the contrary, a lower dose of esmolol may appear more appropriate in patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In subgroup analysis of hypovolemic patients, colloids are significantly more effective for fluid resuscitation, as they may produce a larger increase in stroke volume than crystalloids. 69 Thus, normal volume can be reached faster with colloids than with crystalloids. In subgroup analysis on elderly patients, the mortality was similar among different types of resuscitation fluids.…”
Section: Discussionmentioning
confidence: 99%
“… 77 Among critically ill patients, exposure to positive or negative fluid balance was associated with higher 1-year mortality compared with euvolemic state. 78 However, the most commonly used static parameters (such as central venous pressure [CVP] or pulmonary artery occlusion pressure [PAOP]) cannot predict volume responsiveness, 69 and echocardiography was recommended to predict and measure fluid responsiveness. 79 Among the included studies, the patients may actually have positive and negative fluid balance, and this may influence the mortality or AKI incidence, which may be more prominent in choosing fluid types on patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the assessment of intravascular volume and optimization of CO and renal blood flow have indicated that conventional monitoring provides insufficient data for adequate fluid management [ 13 16 ]. However, meta-analyses of randomized controlled trials indicate that approaches which include measurement of CO and calculate oxygen delivery to guide intravenous fluid replacement are associated with decreased mortality and postoperative complications [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%